THE ROLE OF USING STEAM TECHNOLOGY IN TEACHING ENGLISH IN PRIMARY EDUCATION (Scientific journal of the Fergana State University, 2024)
This article discusses the role of using STEAM technology in the process of teaching English in primary school, its advantages, as well as the history of STEAM, its essence and content. The modern educational paradigm should serve to develop the skills and competencies of harmonizing cognitive and moral qualities from the lowest level of education, studying man and nature as an integral interconnected system, accustoming to a conscious analysis of the relationships in it, and mutual implementation of natural scientific knowledge and social knowledge. On the other hand, in primary education there is a need to teach students to independently acquire the necessary knowledge, engage in creative activities, generate personal motivation for learning and apply the acquired theoretical knowledge in real life situation. Achieving the formation of knowledge in the personality of each student, starting from primary school, creates the basis for the development of basis and subject competencies at subsequent stages of education.